Análise dos fluxos de CO2 entre a superfície e a atmosfera em diferentes tipos de manejo pastoril no bioma Pampa no sul do Brasil - Bremm, Tiago (2019)
The Pampa Biome is the second smallest biome in Brazil occupying about 2.07% of the national territory. In Rio Grande do Sul state, the Pampa occupies 63% of the territory, which favors cattle raising, an activity that contributes heavily to the state’s economy. Emissions from the agricultural sector in Brazil have been increasing in the last decades driven by the increase of the bovine herd. With this increase, livestock management and production system should improve their yield without unbalance the emission of greenhouse gases (GHG). Different types of livestock systems on the Pampa Biome have been encouraged to mitigate the impact of increasing animal production on GHG emissions. In this sense, this work intends to compare the flows of CO2 under three different cattle grazing management systems in the south of Brazil using the Eddy Covariance technique to determine the fluxes. In the study period, two paired groups were analyzed. Group 1: multi-paddock, rotational grazing (MR) - continuous conservative grazing (MC); Group 2: multi-paddock, rotational grazing (MR) - deferral management (MD). Areas within the Group 1 footprint region were considered to be CO2 sources for the atmosphere, with issuance of 199 g CO2 m⁻² by the MR area and 243 g CO2 m⁻² by the MC area at the end of the analyzed period, 121 days. Areas within the Group 2 footprint region behaved as CO2 sinks, with uptake of 1183,3 g CO2 m⁻² by the MD area and 599,3 g CO2 m⁻² in MR at the end of the 244 days analyzed. The presence of cattle in the flux towers footprint region negatively affected the absorption of CO2, which indicates that periods of rest in the grazing of the paddocks influence the dynamics of the fluxes. These results are important to raise awareness about the preservation of the natural vegetation of the Pampa and can still be used in the entry of agriculture and climate models.